Implementation of B'More Healthy Communities for Kids: process evaluation of a multi-level, multi-component obesity prevention intervention. Issue 6 (7th September 2018) - Ruggiero, C F; Poirier, L; Trude, A C B; Yang, T; Schwendler, T; Gunen, B; Loh, I H; Perepezko, K; Nam, C S; Sato, P; Gittelsohn, J
Abstract: B'More Healthy Communities for Kids was a multi-level, multi-component obesity prevention intervention to improve access, demand and consumption of healthier foods and beverages in 28 low-income neighborhoods in Baltimore City, MD. Process evaluation assesses the implementation of an intervention and monitor progress. To the best of our knowledge, little detailed process data from multi-level obesity prevention trials have been published. Implementation of each intervention component (wholesaler, recreation center, carryout restaurant, corner store, policy and social media/text messaging) was classified as high, medium or low according to set standards. The wholesaler component achieved high implementation for reach, dose delivered and fidelity. Recreation center and carryout restaurant components achieved medium reach, dose delivered and fidelity. Corner stores achieved medium reach and dose delivered and high fidelity. The policy component achieved high reach and medium dose delivered and fidelity. Social media/text messaging achieved medium reach and high dose delivered and fidelity. Overall, study reach and dose delivered achieved a high implementation level, whereas fidelity achieved a medium level. Varying levels of implementation may have balanced the performance of an intervention component for each process evaluation construct. This detailed process evaluation of the B'More Healthy Communities for Kids allowed the assessment of implementation successes, failures and challenges of each intervention component.